2020
DOI: 10.1038/s41598-020-66173-9
|View full text |Cite
|
Sign up to set email alerts
|

Change of rhizospheric bacterial community of the ancient wild tea along elevational gradients in Ailao mountain, China

Abstract: The rhizospheric microbial community is one of the major environmental factors affecting the distribution and fitness of plants. Ancient wild tea plants are rare genetic resource distributed in Southwest China. In this study, we investigated that rhizospheric bacterial communities of ancient wild tea plants along the elevational gradients (2050, 2200, 2350 and 2500 m) in QianJiaZhai Reserve of Ailao Mountains. According to the Illumina MiSeq sequencing of 16 S rRNA gene amplicons, Proteobacteria, Acidobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Southwest China including Yunnan, Guizhou and Sichuan Province has been regarded as the origin center, which is now widely cultivated all over the world for approximately 5000 years [ 4 6 ]. Until now, Lincang, Puer and Xishuangbanna Regions in Yunnan Province, China, still remained abundant ancient tea trees of wild, transitional and artificial culture types, respectively [ 7 , 8 ]. In particular, the fresh tea-leaves collected from the artificial culture trees with an age over 100 years in ancient tea plantations could be processed for Pu-erh tea, black tea and white tea [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Southwest China including Yunnan, Guizhou and Sichuan Province has been regarded as the origin center, which is now widely cultivated all over the world for approximately 5000 years [ 4 6 ]. Until now, Lincang, Puer and Xishuangbanna Regions in Yunnan Province, China, still remained abundant ancient tea trees of wild, transitional and artificial culture types, respectively [ 7 , 8 ]. In particular, the fresh tea-leaves collected from the artificial culture trees with an age over 100 years in ancient tea plantations could be processed for Pu-erh tea, black tea and white tea [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…3). A previous study on the tea orchard rhizosphere microbiome of Ailao mountain, China, has demonstrated the dominance of these three major phyla in the rhizosphere of the ancient wild tea along the elevation gradient (Zi et al ., 2020). Moreover, multiple studies have shown the dominance of Proteobacteria and Acidobacteria during long‐term continuous cropping of tea orchards in Anxi County of Fujian Province, China (Li et al ., 2016), and in the rhizosphere of freshly planted (2 years old) and old (30 years old) tea plants in the Anxi county on the south coast of Fujian province, China (Arafat et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, soil pH's positive and negative influence on the tea rhizosphere bacterial community diversity has been reported (Koga, 2003; Han et al ., 2007; Li et al ., 2016; Arafat et al ., 2017). The elevation, tea orchard age, tea cultivation intensity and duration, soil nutritional status have been shown to influence rhizosphere bacterial communities in the tea ecosystem (Li et al ., 2016; Arafat et al ., 2017; Arafat et al ., 2020; Zi et al ., 2020). Most of these studies were carried out on Chinese tea varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Southwest China including Yunan, Guizhou and Sichuan Province have been regarded as the origin center, which is now widely cultivated all over the world for approximately 5,000 years [4][5][6]. Until now, Lincang, Puer and Xishuangbanna Regions in Yunnan Province, China, still remained abundant ancient tea trees of wild, transitional and arti cial culture types, respectively [7][8]. In particular, the fresh tea-leaves collected from the arti cial culture trees of ancient tea plantations with an age over 100 years could be processed for Pu-erh tea, black tea and white tea [8].…”
Section: Introductionmentioning
confidence: 99%